PENGARUH PENGHINDARAN PAJAK DAN RISIKO PAJAK TERHADAP BIAYA UTANG - Holly, Anthony; Lukman; Jao, Robert; Mardiana, Ana; Kasim, Chelsea (Journal of Financial and Tax, 2026)
The purpose of this study is to analyze the effect of tax avoidance and tax risk on the cost of debt. This study is built with an agency theory approach. This study uses secondary data in the form of annual reports of manufacturing companies listed on the Indonesia Stock Exchange for the period 2022-2024. The number of samples is 108 company data for 3 years, which were selected using the purposive sampling method. The results of this study indicate that tax avoidance has a positive and significant effect on the cost of debt. However, tax risk has a positive but insignificant effect on the cost of debt.